TIO Associated with Hyperparathyroidism: A Rarity, a Rule, or a Novel HPT-PMT Syndrome—A Case Study with Literature Review - Michael Salim; Mohannad Samy Behairy; Elena Barengolts (Case Reports in Endocrinology, 2021)
Objective. Association of primary hyperparathyroidism (pHPT) with phosphaturic mesenchymal tumors (PMT) is rarely reported. This report entertains the hypothesis of the causal association of HPT with tumor-induced osteomalacia (TIO) and of the existence of HPT-PMT syndrome. Case Presentation. A 49-year-old man presented with fragility rib fractures, generalized bone pain, and muscle weakness worsening over the past 3 years. Initial tests demonstrated hypophosphatemia and high PTH. The diagnosis of pHPT was entertained, but parathyroid scan was negative. During a 2-year follow-up, the patient reported minimal improvement of symptoms after intermittent treatment with calcitriol and phosphate. Biochemical evaluation showed persistent hypophosphatemia with renal phosphate wasting, elevated FGF23, and osteopenia on DXA scan. TIO was suspected. Multiple MRIs and whole-body FDG-PET scans were inconclusive. The patient subsequently underwent 68Ga-DOTATATE PET-CT, which revealed a somatostatin receptor-positive lesion in the lung. The resected mass was confirmed as PMT. The patient had dramatically improved symptoms, normal phosphate, calcium, and FGF23. During follow-up over 3 years postsurgery, the patient had slowly rising calcium and persistently elevated PTH. Conclusion. The debate whether the patient had pHPT or tertiary HPT prompted literature review showing that aberrant genes including FGFR1, FGF1, fibronectin 1, and Klotho were mechanistically involved in the HPT-PMT association. This case highlights the pitfalls contributing to delayed diagnosis and treatment of TIO and hypothesizes the association between pHPT and PMT.